2012
DOI: 10.4018/jal.2012070103
|View full text |Cite
|
Sign up to set email alerts
|

Research Framework for Analyzing the Relationship Between Greening of Suppliers and Green Innovation on Firms’ Performance

Abstract: In recent years, environmental performance has become part of a company’s strategic value. This is partly attributed by the recent regulatory development in this area. For example the WEEE and RoHS directives were enforced by the European Union to require manufacturers to take recycling (and reuse) and selection of material into design consideration. These initiatives exemplify the importance of green supply chain management. Although companies can make use of green supply chain management to create a competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Thirty-nine models/frameworks that address GSCM internal practices have been observed: senior management commitment, support for mid-level managers and cross-functional cooperation for environmental improvement (Chan et al, 2012b;Dey & Cheffi, 2012;Hernandez et al, 2012;Lee et al, 2012;Mitra & Datta, 2014;Prata et al, 2013;Sheu et al, 2005;Zhu, Sarkis, & Lai, 2012), total quality environmental management (Chan et al, 2012b;Giovanni & Vinzi, 2012;Mirhedayatian et al, 2014;Mitra & Datta, 2014;Tsai & Hung, 2009), environmental compliance (Büyüközkan & Çifçi, 2012;Felice et al, 2013;Hernandez et al, 2012;Kuo et al, 2013;Lee & Klassen, 2008;Mirzapour Al-e-hashem & Rekik, 2013;Olugu et al, 2011;Prata et al, 2013;Rao & Holt, 2005;Salam, 2011;Shi et al, 2012;Tang et al, 2012), audit programmes Mirhedayatian et al, 2014;Mitra & Datta, 2014;Singh et al, 2008), ISO 14001 certification Mirhedayatian et al, 2014;Singh et al, 2008), existing environmental management systems (Giovanni & Vinzi, 2012;Green et al, 2012b;Wu, 2013), green manufacturing practice (Chien & Shih, 2007;Dey & Cheffi, 2012;Felice et al, 2012;Golghate & Pawar,...…”
Section: Gscm Variables Considered In the Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-nine models/frameworks that address GSCM internal practices have been observed: senior management commitment, support for mid-level managers and cross-functional cooperation for environmental improvement (Chan et al, 2012b;Dey & Cheffi, 2012;Hernandez et al, 2012;Lee et al, 2012;Mitra & Datta, 2014;Prata et al, 2013;Sheu et al, 2005;Zhu, Sarkis, & Lai, 2012), total quality environmental management (Chan et al, 2012b;Giovanni & Vinzi, 2012;Mirhedayatian et al, 2014;Mitra & Datta, 2014;Tsai & Hung, 2009), environmental compliance (Büyüközkan & Çifçi, 2012;Felice et al, 2013;Hernandez et al, 2012;Kuo et al, 2013;Lee & Klassen, 2008;Mirzapour Al-e-hashem & Rekik, 2013;Olugu et al, 2011;Prata et al, 2013;Rao & Holt, 2005;Salam, 2011;Shi et al, 2012;Tang et al, 2012), audit programmes Mirhedayatian et al, 2014;Mitra & Datta, 2014;Singh et al, 2008), ISO 14001 certification Mirhedayatian et al, 2014;Singh et al, 2008), existing environmental management systems (Giovanni & Vinzi, 2012;Green et al, 2012b;Wu, 2013), green manufacturing practice (Chien & Shih, 2007;Dey & Cheffi, 2012;Felice et al, 2012;Golghate & Pawar,...…”
Section: Gscm Variables Considered In the Frameworkmentioning
confidence: 99%
“…Thirty-two models/frameworks which emphasized environmental performance have been identified: the companies which adopted GSCM reduced emissions of pollutants, use of waste water, solid waste and frequency of environmental accidents (Büyüközkan & Çifçi, 2012;Chan et al, 2012b;Chien & Shih, 2007;Chiou et al, 2011;Felice et al, 2012;Golghate & Pawar, 2012;Jamshidi et al, 2012;Koh et al, 2012;Lin, 2013;Mitra & Datta, 2014;Olugu et al, 2011;Sawadogo & Anciaux, 2011;Sheu et al, 2005;Singh et al, 2008;Zhao et al, 2012) and improvement operating activities (Chan et al, 2012a;Chiou et al, 2011;Dey & Cheffi, 2012;Dou et al, 2014;Felice et al, 2012;Felice et al, 2013;Giovanni & Vinzi, 2012;Golghate & Pawar, 2012;Green et al, 2012a;Green et al, 2012b;Kuo et al, 2014;Lee, 2008;Lee & Klassen, 2008;Olugu et al, 2011;Prata et al, 2013;Rao & Holt, 2005;Sheu et al, 2005;Shi et al, 2012;Tang et al, 2012;Wu, 2013;Zhu, Sarkis & Lai, 2012;Zhu et al, 2013).…”
Section: Performance Variables Considered In the Frameworkmentioning
confidence: 99%
“…Procurement of green materials have high cost but provides economic benefits in disposition activities and environmental protection (Azevedo et al, 2011). Implementation of green practices needs cleaner technology development and advancement (Chan et al, 2012). Luthra et al (2014) identified organizations may attain low cost and environment-friendly manufacturing system by adopting cleaner production technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Identified critical factors for successful adoption of GSCM practices Green procurement, designing & packaging CF4 Kumar & Garg, 2016;Luthra et al, 2014;Eltayeb et al, 2011;Ageron et al, 2012 5 Cleaner technology development & advancement Prakash & Barua, 2015c;Chan et al, 2012;Luthra et al, 2014 6 Green supplier development and certification Luthra et al 2014;Agarwal and Vijayvargy, 2012;Kannan et al, 2014 7 Organizational support for GSCM CF7 Tseng et al, 2012;Muduli et al, 2013;Toppinen and KorhonenKurki, 2013 8 Support & motivation from customers CF8 Zhu et al, 2008;Luthra et al, 2014;Ageron et al, 2012 …”
Section: Tablementioning
confidence: 99%
“…Green innovations in processes aim to make business processes become green, from procurement to production and delivery (Chan, Chiou, & Lettice, 2012). An innovative green process is characterized by its fitness to environmental criteria established by industrial and social contexts in which the company operates as well as those set by the market and consumers which it intends to serve; full consideration of resource and energy use, human toxicity, environmental impact and sustainability issues in the development and implementation of a process/activity; and incorporation of a continuous evaluation of its impact and improvement of mechanisms within the process/activity (Chiou, Chan, Lettice, & Chung, 2011).…”
Section: Green Innovations -Conceptualizationmentioning
confidence: 99%